Gambaran Proses Kegiatan Pos Pembinaan Terpadu Penyakit Tidak Menular di Puskesmas Sempu Kabupaten Banyuwangi (The Description of Activity Process for the Integrated Development Post of Non-Communicable Disease (IDP of NCD) at Sempu Public Health Centre i - Emi Dwi Astuti; Irma Prasetyowati; Yunus Ariyanto (Pustaka Kesehatan, 2016)
Sempu Public Health Centre (PHC) where the IDP of NCD activity was only applied under 1% in 2014 which the fact remains that Sempu PHC ironically is the first PHC which has IDP of NCD in Banyuwangi regency. This research aimed to find out how Posbindu PTM Al-Mubarok activity worked in Sempu PHC. This research used descriptive study with qualitative data supported. The informants of this research were purposively taken which included coordinator surveillance of Health Department in Banyuwangi regency, coordinator IDP of NCD, midwife, nurse, two cadres, the work partners and two IDP of NCD members. This research collected the data by doing interview, attentive observation and triangulation technique. Then, the data gathered were analyzed descriptively. The result showed that activity process of Posbindu PTM Al-Mubarok in Sempu PHC was different with IDP of NCD guidelines. The process did not go well because of the input which included the insufficient of human resources, incomprehensive and minimal training, insufficient of equipments, the lack of public awareness, the financial dependence and the implementation method which was not regularly conducted every month. Keywords: process, IDP of NCD